Hexagonal Boron Nitride Passivation Layer for Improving the Performance and Reliability of InGaN/GaN Light-Emitting Diodes - Lee, Gun-Hee; Cuong, Tran-Viet; Yeo, Dong-Kyu; Cho, Hyunjin; Ryu, Beo-Deul; Kim, Eun-Mi; Nam, Tae-Sik; Suh, Eun-Kyung; Seo, Tae-Hoon; Hong, Chang-Hee (MDPI, 2021)
We introduce a low temperature process for coating InGaN/GaN light-emitting diodes (LEDs) with h-BN as a passivation layer. The effect of h-BN on device performance and reliability is investigated. At -5 V, the leakage current of the h-BN passivated LED was -1.15 x 10(-9) A, which was one order lower than the reference LED's leakage current of -1.09 x 10(-8) A. The h-BN layer minimizes the leakage current characteristics and operating temperature by acting as a passivation and heat dispersion layer. With a reduced working temperature of 33 from 45 & DEG;C, the LED lifetime was extended 2.5 times following h-BN passivation. According to our findings, h-BN passivation significantly improves LED reliability.